KARAKTERISTIK DAN HASIL NITRIDISASI STAINLESS STEEL TIPE 316L DENGAN DAPUR FLUIDISED BED - Astana Widi, I Komang (Teknik Mesin S1 ITN Malang, 2008)
The investigation of 316L austenitic stainless steel with nitriding used laboratory scale of fluidized bed reactor has been done. Nitriding temperature treatment is 500 C with variable process as 1, 3 and 6 hours. Then, this investigation used matalography (Scanning Electron Microscope) showed that AISI 316L is formed nitride hard layer on the surface. This nitride hard layer as advanced of austenite as S phase. This layer is formed in one hour as less effective. The profile of hardnes value is showed that tend increase in longer time processing.